Proteomics analysis of soluble secreted proteins of Lutzomyia longipalpis LL5 cells transfected with a dsRNA viral mimic: insights into cellular defense and repair signals - Martins da Silva, Andrea; Llanos Salamanca, Ilya Violeta; Batista, Michel; Marchini, Fabricio Klerynton; Tempone, Antonio Jorge; Loza Telleria, Erich; Traub-Csekö, Yara Maria (Frontiers in Cellular and Infection Microbiology, 2025)
Sand flies, which transmit diseases like leishmaniases, bartonellosis, and certain viruses, pose a significant public health threat. Our research focuses on the immune responses of Lutzomyia longipalpis, the primary vector for visceral leishmaniasis in the Americas. We use L. longipalpis LL5 cells as a model to study how sand flies respond to pathogens. These cells exhibit robust immune reactions, producing molecules mainly regulated by the Toll, IMD, Jak-STAT, and RNAi pathways. In previous studies, we detected a non-specific antiviral response in LL5 cells following double-stranded RNAs (dsRNAs) transfection. A previous complete secretome of these cells showed molecules resembling an interferon-like antiviral response when transfected with polyinosinic–polycytidylic acid (poly I:C), a synthetic dsRNA analog. In the current study, we analyzed soluble proteins secreted by LL5 cells after poly I:C transfection. Using comparative mass spectrometry, we examined protein composition of conditioned media depleted of exosomes at 24 h and 48 h. Most proteins uniquely expressed in the transfected groups had low abundance compared to the overall expressed proteins. Interactome prediction analysis revealed that at 24 h, the proteins uniquely found in the secretome of the transfected group were involved in RNA degradation and purine metabolism, while at 48 h they were linked to ribosomal proteins and signaling pathways such as Hedgehog, Transforming Growth Factor-beta (TGF-β), and Wingless/integrated (Wnt). We highlight increased abundance of the TGF-β-induced protein ig-h3 (24 h and 48 h), a Toll-like receptor 3 (48 h), and a hemocytin (48 h) in the secretion of transfected groups compared to the controls. We also performed an interaction analysis of proteins more secreted by the treated group at 24 h and 48 h. Unlike the interactome of uniquely identified proteins, few interactions were observed at 24 h, with a predominance of extracellular matrix and cell adhesion proteins. The set of proteins more secreted at 48 h presented more interactions than at 24 h, with emphasis on catabolic processes, including RNA degradation. These findings indicate that poly I:C transfection in LL5 cells induces the secretion of proteins involved in cellular defense and repair, revealing molecules involved in the LL5 non-specific antiviral response.